2015
DOI: 10.1007/s10461-015-1183-y
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity, Dietary Diversity, and Body Mass Index of HIV-Infected Individuals on Antiretroviral Therapy in Rural Haiti

Abstract: Food rations are increasingly offered as part of HIV programs in resource-poor settings, often targeted solely to those with under-nutrition by low body mass index (BMI). This practice does not consider food insecurity, another important risk factor for poor outcomes in people living with HIV/AIDS (PLWH). We analyzed factors associated with low BMI and severe food insecurity in 523 PLWH receiving antiretroviral therapy in rural Haiti using logistic regression. Food insecurity was present in 89 % of individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We found no association between undernutrition, educational level, urban residence, home ownership and access to public municipal goods such as electricity and piped water. Wealth or income of patients on ART has been found to be negatively associated with undernutrition in Haiti [54], and Brazil [55], as was educational status in Senegal [19] and wealth in Tigray, Ethiopia [43]. The lack of association may reflect the largely urban make up of our sample or simply the weakness of these measures in capturing socio-economic status.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We found no association between undernutrition, educational level, urban residence, home ownership and access to public municipal goods such as electricity and piped water. Wealth or income of patients on ART has been found to be negatively associated with undernutrition in Haiti [54], and Brazil [55], as was educational status in Senegal [19] and wealth in Tigray, Ethiopia [43]. The lack of association may reflect the largely urban make up of our sample or simply the weakness of these measures in capturing socio-economic status.…”
Section: Discussionmentioning
confidence: 83%
“…It was found to have weak positive association with malnutrition in Brazil, no effect on low BMI in Haiti, and a negative association with malnutrition in Senegal. In older HIV-infected adults, more advanced age is associated with lower BMI [56] although the evidence is mixed [19,54]. The uncertainty around the impact of age on nutritional status suggests that further study on this topic is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of a balanced and healthy diet, as well as physical activity, are considered to be care measures that contribute to health promotion and are fundamental to keep up physical and emotional health. Such health practices provide improved QL for the individuals, lowering mortality rates and increasing adherence to antiretroviral treatments, which are directly linked to improving the immune system ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A study among HIV-positive and HIV-negative women in Rwanda found that although levels of food insufficiency and low dietary diversity were substantial (46% and 43%, respectively), no significant correlations were found between either of these factors and BMI (Sirotin et al, 2012). Finally, a study in Haiti found that at baseline 89% of PLHIV in a food supplementation trial had either moderate or severe food insecurity, but food insecurity was negatively related to BMI (i.e., as food insecurity level increased, BMI decreased) (Rebick, Franke, Teng, Gregory Jerome, & Ivers, 2016). Given the high prevalence of both household food insecurity and obesity among PLHIV in resource poor settings, our study aims to inform policy, programming, and practice to improve ART adherence and HIV treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%